DETECTION OF DRUG INTERACTION IN GICU (GENERAL INTENSIVE CARE UNIT) AT ONE HOSPITAL IN BANDUNG - Wikaningtyas, Pratiwi; Amalia, Lia; S., Hartini (Acta Pharmaceutica Indonesia, 2011)
ICU defined as an intensive monitoring place and life support activities as well as definite therapy in life-threatens disease patients. In this Unit, patients generally receive treatment from various doctors that a patient can receive a variety of drugs from different doctors (polypharmacy). This unit also has higher frequency of drug demand than the other units in the hospital so the potential or actual drug interactions can occur. This study begins with a retrospective pilot study in ICU, concurrent studies in GICU (General Intensive Care Unit), data analysis and conclusions. Detection of drug interactions concurrently on 185 patients obtained 78 drug interactions that consists of 46 (58.97%) pharmacodynamic interactions and 27 (34.61%) pharmacokinetic interactions.